Do institutional investors drive corporate social responsibility? International evidence - Dyck, Alexander; Lins, Karl V.; Roth, Lukas; Wagner, Hannes F. (Journal of Financial Economics, 2019)
This paper assesses whether shareholders drive the environmental and social (E&S) performance of firms worldwide. Across 41 countries, institutional ownership is positively associated with E&S performance with additional tests suggesting this relation is causal. Institutions are motivated by both financial and social returns. Investors increase firms’ E&S performance following shocks that reveal financial benefits to E&S improvements. In cross section, investors increase firms’ E&S performance when they come from countries with a strong community belief in the importance of E&S issues, but not otherwise. As such, these institutional investors transplant their social norms regarding E&S issues around the world.